Insects on palms - Howard, F. W. (CABI Pub., 2001)
This book reviews the interrelationships between palms and insects, emphasizing the similarities in various world regions. Host plants, distribution and bionomics of representative insects are discussed according to their feeding sites on palms (foliage, flowers, fruits and stems) and their taxonomic groups. Host and distribution records for the most extensively represented insect families on palms are tabulated. Pest management and field techniques are also covered.